Identifying industry practice, barriers, and opportunities for mine rehabilitation completion criteria in western Australia. (1st June 2021) - Kragt, Marit E.; Manero, Ana
Abstract: Around the world, the development of acceptable and achievable completion criteria is a necessary part of mine closure planning and fundamental to the successful transition of mined land to a post-mining use. Without adequate completion criteria, a mining company cannot proceed to the process of relinquishment, which is the ultimate goal of most mine closure processes. Despite the central role of completion criteria, there is still a need to build capacity and understanding of how to set targets and develop measurable completion criteria that are accepted by all stakeholders involved. We investigate how completion criteria are currently developed in one of Australia's major mining jurisdictions: Western Australia. Through an industry consultation process that involved interviews and a survey with a total of 102 participants from mining companies, consulting businesses, and relevant regulators, we highlight key challenges and opportunities that the sector faces to successfully define clear, achievable, and agreed completion criteria. This is one of the few industry-wide investigations to capture and analyze the perspectives of stakeholders involved in writing and assessing mine closure completion criteria. Results show that some major challenges included inconsistent coordination within and between stakeholder groups, a lack of knowledge or data about restoration, and an overreliance on status quo practices and post-mining land uses. Our work shows that ongoing research on ecological restoration and technological innovations is necessary, but that additional organizational and regulatory barriers need to be addressed to achieve a consistent, coordinated, multi-stakeholder approach to define completion criteria and to advance successful mine rehabilitation and relinquishment. Highlights: Previous research on mine rehabilitation targets ecological restoration and technological knowledge gaps. Our interviews and industry survey reveal critical organizational and regulatory barriers to effective rehabilitation. Lack of coordination within and between industry and regulators are hindering progress. Inability to define completion criteria is impeding mine closure and relinquishment. We recommend more collaborative, transparent approaches across stakeholders.